2021
DOI: 10.1111/mec.16013
|View full text |Cite
|
Sign up to set email alerts
|

The demographic history of Castanea sativa Mill. in southwest Europe: A natural population structure modified by translocations

Abstract: In domesticated species, translocation of materials can alter natural demographic patterns; this may have occurred in Castanea sativa (European chestnut), a species conserved in several refuges, with a long domestication history for nut production. Bayesian analysis of population genetic structure in marginal areas and in the centre of C. sativa range, considering spatial information and making corrections for unbalanced size, allowed visualization of a genetic structure that was subsequently analysed by appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 129 publications
0
11
0
Order By: Relevance
“…The species was extensively cultivated in southern Europe for nuts and timber since the Roman Empire (Fernández‐López et al, 2021; Krebs et al, 2019; Marinoni et al, 2013; Mattioni et al, 2017). Recent studies revealed significant translocation of germplasm between the Iberian and Apennine peninsulas (Fernández‐López et al, 2021) and a considerable gene flow between cultivated orchards and natural populations in the Adriatic region (Tumpa et al, 2022). However, sweet chestnut is also found isolated in the Caucasus ecoregion, a global biodiversity hotspot (Tarkhnishvili et al, 2012; Zazanashvili et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The species was extensively cultivated in southern Europe for nuts and timber since the Roman Empire (Fernández‐López et al, 2021; Krebs et al, 2019; Marinoni et al, 2013; Mattioni et al, 2017). Recent studies revealed significant translocation of germplasm between the Iberian and Apennine peninsulas (Fernández‐López et al, 2021) and a considerable gene flow between cultivated orchards and natural populations in the Adriatic region (Tumpa et al, 2022). However, sweet chestnut is also found isolated in the Caucasus ecoregion, a global biodiversity hotspot (Tarkhnishvili et al, 2012; Zazanashvili et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…(sweet chestnut), a relict Neogene tree species with a long history of domestication around the Mediterranean Basin. The species was extensively cultivated in southern Europe for nuts and timber since the Roman Empire (Fernández‐López et al, 2021; Krebs et al, 2019; Marinoni et al, 2013; Mattioni et al, 2017). Recent studies revealed significant translocation of germplasm between the Iberian and Apennine peninsulas (Fernández‐López et al, 2021) and a considerable gene flow between cultivated orchards and natural populations in the Adriatic region (Tumpa et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that 70% of the C. sativa genotypes and the 40% of progenies from Montseny inoculated with C. parasitica showed a response analogous to the one of C. mollissima in their canker development. These results are relevant because the chestnut orchards in Montseny are not described as having been introgressed with Asian materials as in other Spanish areas [35]. Their ancestry and traditional management in the last 100 years do not indicate the entry of foreign fruit varieties.…”
Section: Discussionmentioning
confidence: 84%
“…Chestnut (Castanea sativa Mill.) is a temperate thermophilic tree distributed throughout the Mediterranean basin in natural, semi-natural, and managed stands of considerable environmental, cultural, and economic value (Fernández-López and Alía, 2003;Conedera et al, 2004;Fernández-López et al, 2021). Its main area of distribution in 10.…”
Section: Introductionmentioning
confidence: 99%
“…Its main area of distribution in 10. 3389/ffgc.2022.1072661 Spain is in the humid northwest region, as well as scattered stands in central and southern Iberia, where high temperatures are frequent (Fernández-López et al, 2021). Chestnut forests in Spain are threatened by global warming (e.g., May and July air temperatures hit a record high in 2022), providing an ideal testbed for studying heat stress effects.…”
Section: Introductionmentioning
confidence: 99%